PERBEDAAN FATWA DAN QADA SERTA IMPLEMENTASINYA DI INDONESIA - Andi Muh. Taqiyuddin BN; Abdul Syatar (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2022)
The purpose of this research is to explain the meaning of Fatwa and Qada, how are the similarities and differences between fatwa and qada and their implementation in Indonesia, and to explain how the wisdom of fatwa and qada is. This research is qualitative, the type of research is library research and uses phenomenological and normative approaches. The results showed that; 1) The word fatwa comes from Arabic, which means the answer to what is the problem of syarak or legislation. The word Qada comes from Arabic, which means law and determination. It can be understood that the meaning of a fatwa in the term is the answer to the explanation of the mufti regarding religious questions or problems asked by someone or mustafti. The meaning of Qada in terms is a legal decision from qadi regarding cases or events based on arguments and evidence through mechanisms, the scope of qada is limited and is binding and obligatory. 2) The brief similarity of both of them is both legal products and determined based on the Quran and Hadith. First, the fundamental difference between the two is that fatwas are not binding while qada is binding/force. Second, that the scope of coverage of fatwas is wider than qada. Fatwa application in Indonesia is more dominant than qada. 3) The honesty of Fatwa and Qada can be seen from the existence of the arguments which make it conducive, it is the arguments that position the fatwa and Qada as two legal matters as part of Islamic law, especially Islamic justice.